Mycale micracanthoxea nov. spec. (Porifera, Poecilosclerida) from the Netherlands - Buizer, D.A.G.; Van Soest, R.W.M. (Netherlands Journal of Sea Research, 1977)
Mycale micracanthoxea nov. spec. is described from the Oosterschelde area (SW part of The Netherlands). The Dutch specimens were previously identified as Mycale contareni, but comparison with live French specimens of this species revealed specific differences. The new species is unique in the genus Mycale because of the presence of tiny (7 to 8.5 µm) acanthoxea. The new species is compared with the Mycale species known to occur in the eastern North Atlantic, and its distribution is described.